The Effect of Transport Infrastructure on Land-use Change: The Case of Toll Road and High-Speed Railway Development in West Java - Wilmar Salim; Uly Faoziyah (Journal of Regional and City Planning, 2022)
The development of the Cipularang Toll Road and the Jakarta-Bandung high-speed railway (HSR) in West Java Province in Indonesia is expected to boost economic growth and provide equitable development, especially from Jakarta to the regencies and cities in West Java. Such large-scale infrastructure developments cause massive changes in land use in the surrounding areas. These impacts are often not anticipated in spatial planning. This study aimed to identify the effect of transport infrastructure development on land-use change in West Java by using cellular automata. It was found that transport infrastructure development has significant impact on the structure and spatial patterns that lead to the formation of a mega-urban region connecting the Jakarta Metropolitan Area and the Greater Bandung Metropolitan Area.